Prophylactic leg wrapping in elective cesarean section under bupivacain spinal anesthesia - Sharma, SA; Prasad, PN; Marhattha, MN; Gupta, MP (Journal of Institute of Medicine Nepal, 2007)
Background: Hypotension is the most frequent and serious complication associated with spinal anesthesia in obstetrics. Over the years many interventions have been tried to prevent the hypotension. Preloading with fluid, prophylactic vasopressors and leg wrapping have been seen as effective interventions. Leg wrapping, a non invasive and a non pharmacologic method, has consistently been seen as an easy and effective intervention. Various studies using Esmarch bandage, graduated compression bandage and inflatable boots are found in the literature. Till now no study has been done using Elastic leukocrepe bandage, which is cheap and widely available. This study was thus carried out with the aim of finding out if wrapping with elastic leukocrepe would have a similar effect. Methods: In a randomized controlled study, 30 patients (15 in each group) had either their legs wrapped or no wrapping prior to spinal anesthesia before cesarean section. Systolic blood pressure and rescue mephentermine use were recorded. Result: The mean systolic blood pressure, SBP, at different time intervals was compared. The leg wrapped group had consistently higher SBP. Overall, 12 out of 15 patients in the leg wrapped group and all 15 patients in the control group experienced hypotensive episodes requiring rescue dose of mephentermine. The number of patients who had more than one hypotensive episodes during the surgery was also analyzed. 5 out of 15 cases compared to 14 out of 15 controls had more than one hypotensive episodes requiring supplemental mephentermine. Conclusion: The findings of my study suggest that the wrapping of lower limbs with Leukocrepe elastic bandage (like other methods of wrapping) decreases the incidence of hypotensive episodes to a significant degree however it does not eliminate the incidence of hypotension in spinal anesthesia given to elective cesarean section patients. Key Words: prophylactic leg wrapping, elective CS, spinal anesthesia. The full text of this paper is available at Journal of Institute of Medicine website